Anesthetic considerations in patients with cystic pulmonary adenomatoid malformations - Bhavna Gupta; Kapil Chaudhary; Nitin Hayaran; Sujoy Neogi (Wolters Kluwer Medknow Publications, 2021)
Congenital pulmonary adenomatoid malformation (CPAM) is a rare entity. The authors searched the US National Library of Medicine Database, EMBASE, Google Scholar, PubMed Central for anesthetic management in CPAM. The search was performed using the terms: congenital cystic adenomatoid malformation, congenital pulmonary adenomatoid malformation, CCAM, CPAM, anesthetic management. The prognosis of CPAM depends on timely diagnosis, presence of hydrops, degree of hypoplasia of remaining lung, and the size of the lesion. Symptomatic patients must be treated surgically and lobectomy is considered the gold standard. Anesthetic management of such cases is challenging as it involves thoracotomy or thoracoscopic lobectomy or cystectomy and can lead to sudden hemodynamic Collapse. Early extubation should be considered to avoid iatrogenic ventilator-induced bronchial stump dehiscence resulting from positive pressure ventilation.